IMPLIKASI ACFTA (ASEAN CHINA FREE TRADE AREA) TERHADAP PERKEMBANGAN UMKM (USAHA MIKRO KECIL DAN MENENGAH) DI INDONESIA - Rimapradesi, Yulia; Hidayat, Regga Fajar; Alif, Naufal Muhammad (Economic and Science Faculty of Islamic State University, 2023)
ACFTA (ASEAN China Free Trade Area) is one of the collaborations built by Indonesia in the context of improving the domestic economy, in which Indonesia must follow the free trade policies and regulations set by the WTO (World Trade Organization). Indonesia's readiness to face this free trade is highly questionable. This also has an impact on MSMEs (Micro, Small and Medium Enterprises) in Indonesia, with the existence of free trade, trade competition is getting hotter. This article aims to look at the implications of ACFTA (ASEAN China Free Trade Area) on the development of Indonesian SMEs. Qualitative research with analytical descriptive methods is applied in this study, based on data sources obtained through library research techniques. This study shows that the implication of ACFTA (ASEAN China Free Trade Area) is not contributing to the economic improvement of MSMEs (Micro Small and Medium Enterprises) this is inseparable from the government factor which is more concerned with Chinese imports and the lack of understanding of marketing for MSMEs (Micro, Small and Medium Enterprises)